Analysis of Elementary School Students' Mathematical Anxiety Levels - Jannah, Nurul Misbahul; Halim, Abdul; Asmara, Syinta Bella (Journal of Indonesian Primary School, 2024)
The aim of this research is to measure students' anxiety levels regarding mathematics learning at the elementary school level in the city of Banda Aceh. This research uses a quantitative approach with a survey research type. This research was conducted on all elementary school students in the city of Banda Aceh with a sample of 90 students. The sampling technique used in this research was cluster random sampling. This research data uses a questionnaire. The data obtained is quantitative data which is then analyzed using descriptive analysis techniques. The results of this study show that the level of mathematics anxiety in elementary school students has an average score of 62.58%. The students' highest mathematics anxiety score was 92.18%, which means they fall into the very high anxiety level category. The lowest score achieved for students' mathematics anxiety was in the high category, because the score obtained was 53.12%. Based on the results of this research, we can conclude that the level of mathematics anxiety that occurs in elementary school students in the city of Banda Aceh is in the high level of mathematics anxiety category.